Revitalizing minority languages using music: Three South-Guan languages of Ghana in focus - Ansah, Mercy Akrofi; Agyeman, Nana Ama; Adjei, Godwin (Research Journal in Advanced Humanities, 2022)
Several interdisciplinary researchers have been interested in the relationship between language and music thus producing several works in quest of this interdisciplinary connection. This study, on the other hand, attempted to examine how music may be utilized to reinvigorate the understudied minority languages. It focuses on three South Guan languages: Leteh, Kyerepong and Efutu. Studies done in this area have observed that in notable respects, language and music are systematically comparable. For instance, the two are similarly constructed of functional and meaningful units; both possess phonemic and morphemic properties. Furthermore, the phonemic and morphemic units/properties are used to produce utterances by rules of sequencing and re-combination. This study draws on the Affective Filter Hypothesis (Krashen, 1982) which emphasizes the importance of positive emotions in language acquisition. Language surveys were conducted in Winneba, Larteh and Adukrom where the three languages are spoken. The study concludes that the principle behind the use of songs in teaching a second language can be extended to the teaching/learning of less-studied languages/minority languages and ultimately, their revitalization.